Progresivitas Alumni Ma’had Aly As’adiyah Sengkang dalam Menguatkan Pendidikan Moderasi Islam - Abd. Haris; Nurfaika (Innovations in Multidisciplinary Education Journal, 2024)
Pesantren’s pedagogy is designed to apply and develop educational patterns that can direct and strengthen the values of pesantren, without having to abandon the educational methods that have existed for a long time. Ma'had Aly As'adiyah has an important role in innovating and exploring the knowledge gained through education and dakwah of moderation as the basis for the development of religious teachings in society. Pesantren is not only a formal institution to strengthen the nation and state. But it also became a patron of the integrity of the future generations of the nation. His independence and essential strength have been formatted with spiritual roots that will never waver. So, it is not surprising that the output of a pesantren becomes a reference. That's because it sees the intellectualism of pesantren which has developed quite dynamically, competitively, civilized and advanced. The changes it brings will advance through education and dakwah of moderation as a unifier of the people. Pesantren’s education becomes a pattern in itself, namely education that is directed to spread wasatiyah without abandoning the old methodology. The existence of Ma'had aly as'adiyah Sengkang, for example, has become a media "agent of change" in the midst of a society that is confused about the current religious situation. The spiritualism of pesantren already has strong roots to uplift the people. Its existence in the midst of society became a special happiness for its people, especially in the branches of As'adiyah.  This paper will see how the participation and contribution of Ma'had Aly As'adiyah Sengkang alumni in realizing social transformation through education and da'wah wasaty in branches of As'adiyah spread across Indonesia. This type of research is qualitative-descriptive which is supported by the results of interviews, observations and analysis of documents that have been processed and concocted to become a valuable research.